2018
DOI: 10.3928/01477447-20181023-01
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Clinical Outcomes of Hemiarthroplasty With Concentric Glenoid Reaming: The Ream and Run Procedure

Abstract: The purpose of this study was to evaluate the short-term clinical and radiographic outcomes of humeral hemiarthroplasty and concentric glenoid reaming (“ream and run” procedure) and to compare the outcomes with those of total shoulder arthroplasty (TSA) for glenohumeral arthritis. Patients with glenohumeral arthritis who underwent the ream and run procedure with a minimum follow-up of 2 years were retrospectively reviewed. The primary outcome was revision to TSA. Secondary outcome measures included functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As a result, the outcome of the procedure may be strongly influenced by the status of the patient and the shoulder prior to surgery: patients with higher levels of function before surgery are more likely to be satisfied with their outcomes postoperatively 26 . Many patients having the RnR procedure have levels of postoperative function that are equal to or better than those for aTSA 16,23,26,27,30,34,38,48,50,51,[56][57][58][59][60][61][62][63][64] (Fig. 6, Table I).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the outcome of the procedure may be strongly influenced by the status of the patient and the shoulder prior to surgery: patients with higher levels of function before surgery are more likely to be satisfied with their outcomes postoperatively 26 . Many patients having the RnR procedure have levels of postoperative function that are equal to or better than those for aTSA 16,23,26,27,30,34,38,48,50,51,[56][57][58][59][60][61][62][63][64] (Fig. 6, Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The ream-and-run procedure combines HA with concentric spherical glenoid reaming to correct glenoid articular surface incongruity in order to recenter the humeral head and create durable glenoid articulation without implant or graft [46][47][48][49][50][51][52][53]. The procedure provides an alternative to TSA using a conventional all-polyethylene glenoid implant.…”
Section: Discussionmentioning
confidence: 99%
“…Its development was motivated by concerns over early glenoid implant loosening, especially in younger, more active patients, and the unpredictable results following either glenoid implant removal or revision implantation [ 49 ]. Recent studies have demonstrated higher rates of return to sports and strenuous work following ream-and-run compared with TSA [ 48 , 52 ]. In our series, one patient with severe bilateral posterior glenoid erosion and dysplasia underwent staged bilateral ream-and-run procedures at 20 and 24 years of age to partially correct glenoid version and create a smooth articulation.…”
Section: Discussionmentioning
confidence: 99%
“…17 The "ream-and-run" procedure in which the glenoid is prepared to create a concentric surface also has had inconsistent results. 10,[18][19][20] Of particular concern with hemiarthroplasty is that revision to total shoulder arthroplasty may be necessary, and evidence shows that pain relief and improvements in function are not as robust as when total shoulder arthroplasty is performed as a primary procedure. [20][21][22] Asymmetric reaming is a technique in which the "high side" of the anterior glenoid is reamed to correct glenoid retroversion and recenter the humeral head prior to resurfacing the glenoid with an implant.…”
Section: Treatment Optionsmentioning
confidence: 99%
“… 17 The “ream-and-run” procedure in which the glenoid is prepared to create a concentric surface also has had inconsistent results. 10 , 18 20 Of particular concern with hemiarthroplasty is that revision to total shoulder arthroplasty may be necessary, and evidence shows that pain relief and improvements in function are not as robust as when total shoulder arthroplasty is performed as a primary procedure. 20 22 …”
Section: Treatment Optionsmentioning
confidence: 99%